Formation of Global HR Strategies in the Conditions of Transnationalisation of Business - VEDERNIKOV, Mykhailo; CHERNUSHKINA, Oksana; VOLIANSKA-SAVCHUK, Lesia; HORBATIUK, Oleksandr (University Scientific Notes, 2026)
The article explores the theoretical and practical aspects of the formation of global HR strategies in the context of business transnationalisation. The concept of transnationalisation as a defining characteristic of the current stage of globalisation development is explored, and current trends in the transnationalisation of the world economy are highlighted. It is noted that the main challenges of business transnationalisation include differences in the legal and regulatory environment of different countries, the complexity of managing and coordinating international activities, financial and political risks, increased competition in local markets, difficulties in logistical support, the need to adapt business models to local conditions, data protection, compliance with ethical norms and ensuring corporate social responsibility. The impact of globalisation processes on the transformation of HR management systems, on changing approaches to HR policy, and on strengthening the role of human capital in ensuring the competitiveness of companies in international markets is substantiated. The main factors influencing the formation of global HR strategies are identified, in particular, the digitalisation of the economy, international employee mobility, intercultural interaction, the development of talent management, and the need to adapt HR practices to the local operating conditions of international companies. Global HR strategies are systematised in the context of business transnationalisation, which contributes to a deeper understanding of the tools for ensuring the company’s competitive advantages in the conditions of a modern, integrated and high-tech economic space. Modern approaches to strategic HR management in the international business environment are characterised, and the features of combining global standardisation of HR processes with local adaptation of personnel decisions are revealed. This necessitates the need to demonstrate a high level of flexibility and the ability to adapt to the socio-cultural, legal and economic specifics of different labour markets. It is emphasised that at the present stage, the globalisation of the labour market for Ukraine has become an important tool for integration into the world economy through the development of human potential. In the conditions of war, business relocation and large-scale migration, a new employment model is being formed, in which remote work, international recruitment and export of intellectual services play a key role, which are fundamental factors in ensuring the economic stability of the state. In conclusion, it is noted that strategic HR management is becoming a key tool for ensuring the stability and competitiveness of international business. The implementation of global HR strategies allows for optimising the use of intellectual capital and synchronising the interests of personnel with corporate goals. The need for further improvement of strategic HR management mechanisms in the context of dynamic changes in the global labour market and increased international competition was noted.